2001
DOI: 10.1038/sj.ejcn.1601114
|View full text |Cite|
|
Sign up to set email alerts
|

The occurrence of trans-18:1 isomers in plasma lipids classes in humans

Abstract: Objective: The aim of this study was to examine the distribution of trans fatty acids (TFA) in plasma lipid classes and the relationship with dietary intake of TFA. Design: After a 2 week baseline (habitual) diet, all subjects consumed a moderate fat (MF) diet for 3 weeks with the fat being derived mainly from margarine and the rest from lean beef, and then a very low fat (VLF) diet for 3 weeks with the TFA being derived only from the lean beef. Blood samples were collected 2 days prior to the end and also on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, very few studies have reported the individual TFA isomers in plasma, let alone in each lipid fraction (29,30). We recently reported (31) a combination of methods that could be used to methylate the CLA content of various plasma lipid fractions.…”
mentioning
confidence: 99%
“…However, very few studies have reported the individual TFA isomers in plasma, let alone in each lipid fraction (29,30). We recently reported (31) a combination of methods that could be used to methylate the CLA content of various plasma lipid fractions.…”
mentioning
confidence: 99%
“…Dietary intake of TFA can be estimated based on the TFA levels in plasma phospholipids [40,[42][43][44][45]. Besides, the impact of a mild oxidative event like a typical pregnancy [24][25][26][27] on TFA generation remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Also, plasma phospholipid fatty acids reflect short-term dietary fat intake (1-2 weeks) compared to erythrocyte membrane phospholipids (1-2 months) or adipose tissue fatty acids (years) [54]. However, it has been shown that plasma phospholipid TFA may be used to estimate TFA intake [55]. Although capillary GC is a commonly used method for the determination of TFA, this technique also has its own limitations related to transesterification and temperature settings [56].…”
Section: Discussionmentioning
confidence: 99%